Avaliação in vitro da atividade antibacteriana do diclofenaco sódico frente às cepas de Staphylococcus aureus resistente a meticilina (SARM) - Queiroz, Helaine Almeida (2021)
In recent years, an increase in the incidence of infections caused by bacteria has been reported, including Staphylococcus aureus which corresponds to 50% of infections found in various regions of the world. Currently, the drugs available for the treatment of Methicillin-resistant Staphylococcus aureus (MRSA) are limited and this microorganism has developed resistance to practically all antibiotics indicated for its treatment. This fact is mainly associated with some of its virulence factors, such as hemolysins, staphylococcal enterotoxins, toxic shock syndrome toxin 1 (TSST-1), Panton–Valentine leukocidin (PVL) and its ability to form biofilm that presents up to a thousand times more resistance when compared to its plactonic form. Therefore, it is necessary to search for new therapeutic options and an adequate repositioning of drugs. Drug repositioning is a therapeutic alternative, as it optimizes time and reduces costs when compared to the implantation of a new molecule on the market. The aim of the study was to evaluate the antimicrobial activity of diclofenac sodium alone and in combination with oxacillin against plactonic cells, antibiofilm and biofilm formed in clinical strains of SARM. For this, the antibacterial effect was demonstrated through microdilution, following the recommendations of the protocol M07-A10, Clinical and Laboratory Standard Institute (CLSI) and to determine its possible mechanism of action, flow cytometry was used. MRSA strains showed Minimum Inhibitory Concentrations (MICs) ranging from 156.25 to 1250 μg/mL, synergism with oxacillin occurred in 13 strains (80%) and synergism was also seen against antibiofilm and in biofilm formed from MRSA. Cytometry tests showed that these drugs alter the integrity of the membrane and promote damage to the DNA of SARM cells, leading them to a possible apoptotic process.